2017
DOI: 10.1039/c6md00607h
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of many circular and leaderless bacteriocins are similar to those in saposins and saposin-like peptides

Abstract: Bacteriocins are potent antimicrobial peptides that are ribosomally produced and exported by bacteria, presumably to aid elimination of competing microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 82 publications
(111 reference statements)
0
30
0
1
Order By: Relevance
“…2 and Table 1), the representative of the group, which has been characterized in Enterococcus faecalis strains from both food and clinical origins (68). Circular bacteriocins share a common, highly compact three-dimensional structural fold, which typically consists of an arrangement of 4 -5 ␣-helices, packed into a helical bundle or a saposin-like fold (67,69). Circular bacteriocins have been proposed to kill bacteria by interaction with the bacterial cell membrane, causing its permeabilization and leading to leakage of ions, dissipation of membrane potential, and cell death.…”
Section: Jbc Reviews: Microbial Ribosomal Peptide Natural Productsmentioning
confidence: 99%
“…2 and Table 1), the representative of the group, which has been characterized in Enterococcus faecalis strains from both food and clinical origins (68). Circular bacteriocins share a common, highly compact three-dimensional structural fold, which typically consists of an arrangement of 4 -5 ␣-helices, packed into a helical bundle or a saposin-like fold (67,69). Circular bacteriocins have been proposed to kill bacteria by interaction with the bacterial cell membrane, causing its permeabilization and leading to leakage of ions, dissipation of membrane potential, and cell death.…”
Section: Jbc Reviews: Microbial Ribosomal Peptide Natural Productsmentioning
confidence: 99%
“…Tryptophan residues are known to be involved in protein folding as well as to have a tendency for burial at the bilayer interface . Another common feature of circular and leaderless bacteriocins is the presence of solvent‐exposed tyrosine or tryptophan residues that are likely to facilitate membrane penetration . A comparison of the modeled structure of Lacticin Q with the NMR structure of Enterocin 7A showed that the aromatic side chains located at different positions in the sequences were seen at structurally equivalent locations in the two structures.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of solvent exposed residues using GETAREA 44 reveals that the N-to C-linkage of all these bacteriocins except the micelle embedded acidocin B is buried in the protein core (the ratio of side chain surface area to the average solventaccessible surface area of the first and last amino acid, respectively is less than 20%). Unlike saposins and saposin-like peptides which are stabilised by disulfide bonds between cysteine residues 45 , the bacteriocin helical fold appears to be stabilised by hydrophobic side chain interactions upon peptide circularisation 43 . Martin-Visscher, et al 43 proposed that hydrophobic residues close to the N-C linkage may play a role in the interaction between the linear peptide and the cyclisation enzyme, helping to bring the termini into close proximity for cyclisation to take place.…”
Section: Structural Comparisons Of Circular Bacteriocinsmentioning
confidence: 99%
“…Some hydrophobic residues are exposed at the surface of the molecules (Figure 2, right panel). The hydrophobicity of these peptides is thought to be crucial for creating pores in the bacterial membrane, especially for family II bacteriocins as they are less cationic 28,45 (Table 2). Permeation of the cell membrane by these peptides causes leakage of ions, dissipation of membrane potential and eventually cell death 8 .…”
Section: Surface Characteristics Of Circular Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation